Research progress on treatment of renal anemia in patients with chronic kidney disease - Li Yudong, Liao Wenjian, Luo Yonghang, Chen Qiuyu, Su Yong (Xin yixue, 2023)
Renal anemia is a prevalent complication of chronic kidney disease （CKD）， which severely affects the prognosis of patients. The pathogenesis of renal anemia is complicated， and the core of which is erythropoietin deficiency and iron metabolism disorder. For years， renal anemia has been mainly treated based on erythropoiesis-stimulating and iron agents. Blood transfusion is used as a remedial treatment. Other therapeutic interventions include alleviating malnutrition， supplementing folic acid and vitamin B12， adequate dialysis and controlling hyperparathyroidism， etc.， which yield low efficacy. In recent years， clinical application of hypoxia-inducible factor prolyl hydroxylase inhibitors has brought another innovation in the treatment of renal anemia， and some potential approaches for the treatment of renal anemia have been reported. In this article， recent research progresses upon the treatment of renal anemia in CKD patients were reviewed， aiming provide new ideas for clinical treatment of this disease.